ONSET OF CURRENT MILANKOVITCH-TYPE CLIMATIC OSCILLATIONS IN LAKE BAIKAL SEDIMENTS AT AROUND 4 MA - Kashiwaya K.; Ochiai S.; Sakai H.; Kawai T. (My University, 2003)
Low summer insolation would increase Northern Hemisphere ice sheets only if winter snow persisted all year. Lake Baikal records reveal that such a climatic threshold may have been reached at around 4.0 Ma. Insolation minima at about 3.9, 3.8 and 3.7 Ma, which were obliquity-related, may have triggered Milankovitch-type climatic oscillations characterized by orbital cycles (with periodic major Northern Hemisphere ice sheets). Intensification of these oscillations at about 2.8 Ma was probably connected to another decrease in insolation (i.e. another obliquity-related insolation minima), and seemingly triggered larger oscillations in the prevailing climatic regime of the late Pliocene and Pleistocene.
Keywords: LAKE BAIKAL; INSOLATION; NORTHERN HEMISPHERE GLACIATION; Pleistocene; Pliocene; Cenozoic::Quaternary::Pleistocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Кайнозой::Четвертичная::Плейстоцен